Colorectal cancer follow-up: An intervention to support patients following treatment - Ngune, Irene Marigu (Curtin University, 2015)
With an increasing numbers of patients treated for colorectal cancer (CRC), strategies that support existing services are required. This thesis outlines a series of studies including GPs’ approaches to treating CRC problems, plus the development and trial of a self-assessment tool (SATp) to support patients who consult their GPs regarding CRC-related health problems. Overall, using SATp with general practice support is a viable method to support CRC patients with problems following cancer treatment.